2007
DOI: 10.22358/jafs/66794/2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rice straw in the diet for growing goats on site and extent of digestion and N balance

Abstract: Effect of reducing dietary rice straw on N balance, site and extent of digestion, and efficiency of microbial protein synthesis were evaluated in this trial. Four Liuyang black goats (average body weight 19.3±2.1 kg), fitted with the ruminal, proximal duodenal and terminal ileal cannulas were used in a 4×4 Latin square design. Goats were assigned to four dietary treatments designed by increasing maize grain inclusion at the expense of rice straw: 1. 40% forage (20% maize stover and 20% rice straw, HR); 2. 35% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
3
5
1
Order By: Relevance
“…The DM intake of goats ranged from 567.8-568.6 g/d, which was a little higher than the 506-507 g/d observed previously (Zhao et al, 2007). The increased feed intake was due to the increased proportion of rice straw in the TMR (Zhao et al, 2007). This study corroborated results from elsewhere on the effects of particle size on feed intake.…”
Section: Feed Intakesupporting
confidence: 84%
See 2 more Smart Citations
“…The DM intake of goats ranged from 567.8-568.6 g/d, which was a little higher than the 506-507 g/d observed previously (Zhao et al, 2007). The increased feed intake was due to the increased proportion of rice straw in the TMR (Zhao et al, 2007). This study corroborated results from elsewhere on the effects of particle size on feed intake.…”
Section: Feed Intakesupporting
confidence: 84%
“…When compared with our previous results (Zhao et al, 2007), ruminal OM digestibility was not significantly different with increased proportions of rice straw in the TMR (i.e. 50.4-55.5% vs. 51.2 -56.5%), but the intestinal and total tract OM digestibility (i.e.…”
Section: Digestibilitycontrasting
confidence: 74%
See 1 more Smart Citation
“…Variables of N metabolism are showed in Table 3. The N intake, absorbed N, total tract N digestibility, microbial protein synthesis efficiency were ‘12.11–12.16 g/day’, ‘9.74–10.33 g/day’, ‘80.44–85.55 %intake’ and ‘2.3–2.7 g N/100 g of OMDA’, respectively, in a previous study of increased proportion of rice straw (5–20%) in TMR (Zhao et al . 2007), and were greatly higher than in our study with 40% in TMR.…”
Section: Resultsmentioning
confidence: 92%
“…Increasing the level of rice straw in the diet leads to an increased dietary neutral detergent fibre (NDF) content. Studies have shown that increasing dietary rice straw negatively affects nutrient digestibility in ruminants (Fimbres et al, 2002;Zhao et al, 2007). However, increasing dietary NDF content may have a positive effect on the maintenance of normal rumen function, which is associated with adequate salivation, optimal pH for cellulolytic microorganisms and energy supply (Jaster and Murphy, 1983;Allen, 1997;Krause et al, 2002).…”
Section: Introductionmentioning
confidence: 99%